2014
DOI: 10.1016/j.chembiol.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoded Fluorescent Biosensors for Live-Cell Visualization of Protein Phosphorylation

Abstract: Fluorescence-based, genetically encodable biosensors are widely used tools for real-time analysis of different biological process. Over the last few decades the number of available genetically encodable biosensors and the types of processes they can monitor has increased rapidly. In this review we aim to introduce the reader to general principles and best practices in biosensor development and highlight some of the ways in which biosensors can be used to illuminate outstanding questions of biological function.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 127 publications
(85 reference statements)
0
61
0
1
Order By: Relevance
“…In general, the imaging of biosensor activities in transgenic mice, however, has proven to be more difficult 12 . A problem often encountered with transgenes stably integrated in mice is low-level expression resulting from transgene silencing or recombination events that occur between the highly homologous sequences encoding the sensor FPs 13,14 . Transgenic mice generated by transposon-mediated gene transfer methods have been reported to have higher levels of biosensor expression [13][14][15] .…”
Section: ) Optimized Probes For Tplsmmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the imaging of biosensor activities in transgenic mice, however, has proven to be more difficult 12 . A problem often encountered with transgenes stably integrated in mice is low-level expression resulting from transgene silencing or recombination events that occur between the highly homologous sequences encoding the sensor FPs 13,14 . Transgenic mice generated by transposon-mediated gene transfer methods have been reported to have higher levels of biosensor expression [13][14][15] .…”
Section: ) Optimized Probes For Tplsmmentioning
confidence: 99%
“…A problem often encountered with transgenes stably integrated in mice is low-level expression resulting from transgene silencing or recombination events that occur between the highly homologous sequences encoding the sensor FPs 13,14 . Transgenic mice generated by transposon-mediated gene transfer methods have been reported to have higher levels of biosensor expression [13][14][15] . Transgenic biosensor mice that express a variety of different 6 probes, including sensors of chloride 16 , calcium 17,18 , and voltage 19 , are available commercially (The Jackson Laboratory, Bar Harbor, ME) and might be useful for specific intravital imaging applications.…”
Section: ) Optimized Probes For Tplsmmentioning
confidence: 99%
“…Abovementioned advantages of KAR have thus made these tools amenable for high throughput [61] and led the kinase sensors to be cited as best biosensors in physiology [62]. …”
Section: Amenability Of Fret-based Biosensors For High Throughputmentioning
confidence: 99%
“…In another study, Tang et al demonstrated antigen-antibody interaction via GOD conjugated hollow gold-silver microspheres (AuAgHSs) further coupled using Prussian blue NPs (an artificial catalase), on a graphene-based immunosensor [117]. Pesticidal study [96] Hba1c biosensor Determining glycated hemoglobin [97] Piezoelectric biosensors Detecting carbamate and organophosphate [98] Uric acid biosensors Diagnosis of various clinical abnormalities or illness (e.g., diagnosis of cardiovascular disease) [99,100] Glucose oxidase electrode biosensors Measuring of glucose in biological sample of diabetic patient [101] Quartz-crystal biosensors Detection of proteins at ultrahigh-sensitive level in liquids [102] Optical Polyacrylamide based hydrogel biosensors Immobilization of biomolecules [30] Silicon biosensor For biosensing, bioimaging, and in cancer therapy [103,104] Microfabricated biosensor In novel drug delivery (e.g., in optical corrections) [105] Fluorescence tagged/Genetically encoded biosensor Investigation of various biological process and molecular systems in the cell [27,[106][107][108] Electrochemical or optical Nanomaterials biosensors For diagnosis and in drug delivery [32,93,[109][110][111][112][113][114] …”
Section: Glucose Monitoringmentioning
confidence: 99%